ANALISA AREA GUDANG DENGAN METODE KAIZEN DI PT. INDAH PRAKASA SENTOSA TBK.CAB CILEGON - Hartadi Wijaya (AGUSPATI Research Institute, 2023)
Problem when the company has many waste of time and costs at PT. Indah Prakasa Sentosa tbk. due to lack of attention to the layout goods in a warehouse regions , where many spares not lined up and unsuitable for use in the period 2021-2022 them ,cause just a heap time and money that could prejudice the Company. So, the study aims to get a job next efficiency by an effort to improve the quality of effectively by means of the concepts kaizen , 5s and (PDCA plan , doing , check , and action ). Result this study shows that the percentage for goods the difference is the lack of a record of workers of 57 % , The warehouse narrow is 19 % , lack of the availability of 14 % and the lowest distinction is it because of the landscape of dirty shed as many as 10 %